Pengaruh Reward dan Punishment terhadap Kinerja Karyawan PT Matahari Department Store (Studi Kasus pada MDS 338 Palembang) - Octario, Octario (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
This study aims to analyze the effects of reward and punishment on employees' performance at PT Matahari Department Store 338 Palembang. A total of 133 samples was determined deploying the Slovin formula. Data were collected through questionnaires and observations. This study applied multiple linear regression to analyze the data. The results of the investigation show that each reward and punishment has no significant effect on employees'performance. Likewise, simultaneously reward and punishment have no significant effect on employees'performance. This empirical evidence can provide benefits for PT Matahari Department Store 338 Palembang. To improve employees'performance, the leader of the company can ignore reward and punishment factors.